2016
DOI: 10.1123/jmld.2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Expecting to Teach Enhances Learning: Evidence From a Motor Learning Paradigm

Abstract: There is some evidence that people learn academic (declarative) information better when studying with the expectation of having to teach, but this has not been demonstrated for perceptual-motor skills, which also rely on declarative information but more heavily on procedural knowledge. To address this possibility, participants studied golf-putting instructions and practiced putting with the expectation of having to teach another participant how to putt or the expectation of being tested on their putting. One d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 0 publications
5
44
5
1
Order By: Relevance
“…In academic situations, such as peer tutoring and small group activities, students have a rich opportunity to learn by preparing to teach (or explain) the contents of learning material to others (e.g., tutees, other group members) and teaching others. It is suggested that both preparing to teach and teaching stimulate teacher-role students – namely, students playing the role of tutor or explainer in a learning activity – to process learning material generatively and constructively – for example, selecting, elaborating, and organizing important information from the learning material, integrating newly acquired information with prior knowledge, and reflecting on their own comprehension – and thereby enhance their learning (Annis, 1983; Benware and Deci, 1984; Coleman et al, 1997; van Blankenstein et al, 2011; Fiorella and Mayer, 2013, 2014; Matsuda et al, 2013; Hoogerheide et al, 2014; Nestojko et al, 2014; Daou et al, 2016a; for reviews, see Webb, 1991; Fiorella and Mayer, 2015; Duran, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In academic situations, such as peer tutoring and small group activities, students have a rich opportunity to learn by preparing to teach (or explain) the contents of learning material to others (e.g., tutees, other group members) and teaching others. It is suggested that both preparing to teach and teaching stimulate teacher-role students – namely, students playing the role of tutor or explainer in a learning activity – to process learning material generatively and constructively – for example, selecting, elaborating, and organizing important information from the learning material, integrating newly acquired information with prior knowledge, and reflecting on their own comprehension – and thereby enhance their learning (Annis, 1983; Benware and Deci, 1984; Coleman et al, 1997; van Blankenstein et al, 2011; Fiorella and Mayer, 2013, 2014; Matsuda et al, 2013; Hoogerheide et al, 2014; Nestojko et al, 2014; Daou et al, 2016a; for reviews, see Webb, 1991; Fiorella and Mayer, 2015; Duran, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, participants will be asked to report, in as much detail as possible, any rules, methods, or techniques they recall using to putt during the high -pressure posttest (see Appendix F ). This type of free recall test is frequently used to assess declarative knowledge in motor skill studies ( Daou, Buchanan et al, 2016 ; Daou, Lohse et al, 2016 ; Daou et al, 2018 ; Maxwell, Masters, & Eves, 2000 ; Maxwell, Masters, Kerr, & Weedon, 2001 ; Zhu, Poolton, Wilson, Maxwell, & Masters, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies failed to reveal this effect ( Renkl, 1995 ; Ross & Di Vesta, 1976 ) or demonstrated ambiguous learning effects (enhancements on short-term, but not long-term, test performance; Fiorella & Mayer, 2013 ; Fiorella & Mayer, 2014 ). Daou, Buchanan, Lindsey, Lohse, and Miller (2016) conducted the first investigation into whether expecting to teach enhances learning of motor skills, which rely more heavily on procedural knowledge than academic information does ( Rosenbaum, Carlson, & Gilmore, 2001 ). Daou, Buchanan et al observed having learners practice and study a motor skill with the expectation of teaching it to another person enhanced skill learning in comparison to having learners practice and study a skill with the expectation of being tested, and this effect has been replicated several times ( Daou, Hutchison et al, 2019 ; Daou, Lohse, & Miller, 2016 ; Daou, Lohse, & Miller, 2018 ; Daou, Rhoads, Jacobs, Lohse, & Miller, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations